2001
DOI: 10.1039/b009145f
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cationic phase-transfer catalysts in the oxidation of hydrocarbons by O2

Abstract: The oxidation of tetralin and cyclohexene by was investigated in the presence of cationic phase-transfer O 2 catalysts (PTCs). It was found that the oxidation takes place analogously to the recently investigated catalysed decompositions of hydroperoxide initiator molecules. The natures of both the onium cation and the counteranion are determining factors. The catalytic activity of the onium salt is determined by the e †ective charge on the onium ion and by the size and polarizability of the anion. For both hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…The obtained results correspond very well with previously mentioned publications by many authors about the inhibition by water the hydrocarbons oxidation reactions [31][32][33][34][35][36][37][38][39]. It is known that in keeping with the theory of liquid-phase oxidation the oxidation of hydrocarbons with molecular oxygen occurs by the chain free-radical mechanism and proceeds via a stage of hydroperoxides or peroxides formation, which should participate in a chain branching processes [31][32][33][34].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The obtained results correspond very well with previously mentioned publications by many authors about the inhibition by water the hydrocarbons oxidation reactions [31][32][33][34][35][36][37][38][39]. It is known that in keeping with the theory of liquid-phase oxidation the oxidation of hydrocarbons with molecular oxygen occurs by the chain free-radical mechanism and proceeds via a stage of hydroperoxides or peroxides formation, which should participate in a chain branching processes [31][32][33][34].…”
Section: Resultssupporting
confidence: 80%
“…A number of authors showed that, in the presence of natural surfactants (sulphur, oxygen and nitrogen compounds) in the hydrocarbons medium, hydroperoxides, as amphiphilic compounds possessing surface activity, create H-bonds with the water and, as result of that, absorb on the hydrocarbons/water emulsion boundary with the formation of reverse micelles. Peroxides involved into micelles become more stable and the rate of their decomposition with free radicals formation decreases and as result of that the total reaction rate decreases as well [36][37][38][39]. Csanyi et al reported that in the presence of high water concentrations an overall rate of oxidation decreases, because of the competing formation of the cyclic hydro-peroxide dimers which are kinetically less active [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, palladium could participate in the formation of both allylic radicals [39] and allylic hydroperoxides [85]. Like t-BuOOH and HOOH, these hydroperoxides can epoxide the substrate, reaction that could occur even under metal-free conditions, nevertheless with a low efficiency [14,81,86,87]. Of course, the above reaction pathways possibly apply also to epoxidations summarized in Section 3.1, particularly those in low yields.…”
Section: Peroxides As Oxygen Sourcesmentioning
confidence: 97%
“…3 A very broad variety of homogeneous catalytic systems has been described in the literature for this reaction. [4][5][6][7] It has been also reported that quaternary ammonium halides (and other onium salts, i.e., sulphonium and phosphonium) enhance the solubility of oxygen in the liquid phase, and at the same time show catalytic activity in free radical oxidation reactions, but their role in these processes is not clear. 5,7 In some cases, the explanations invoked to account for the catalytic activity of these compounds point to the possibility to produce free radicals, which is related with the donor effect of the alkyl chains and/or the halide atom of the salt, whereas in other cases the catalytic activity is ascribed to oxygen activation.…”
Section: Introductionmentioning
confidence: 97%